2009
DOI: 10.1002/ceat.200800607
|View full text |Cite
|
Sign up to set email alerts
|

Green Medium for the Hydrolysis of 5‐Cyanovaleramide

Abstract: Hydrolysis of 5-cyanovaleramide (5-CVAM) in near-critical water without the addition of any catalyst has been demonstrated. The results demonstrated that the cyano group at one end of the carbon of 5-CVAM is more reactive than the amide group at the other end, under the same experimental conditions. The relations between 5-CVAM concentration and residence time revealed that hydrolysis of 5-CVAM shows second-order reaction kinetics in the investigated temperature range. The rate constants, average apparent acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…This result suggested that hydrolysis of adipamide proceeded as a consecutive reaction. Based on our experimental results and previous study (Duan et al, 2009), the reaction scheme of the hydrolysis of adipamide is represented in Fig. 6.…”
Section: Reaction Scheme and Kineticsmentioning
confidence: 99%
“…This result suggested that hydrolysis of adipamide proceeded as a consecutive reaction. Based on our experimental results and previous study (Duan et al, 2009), the reaction scheme of the hydrolysis of adipamide is represented in Fig. 6.…”
Section: Reaction Scheme and Kineticsmentioning
confidence: 99%
“…There is a considerable amount of literature on the hydrolysis of amide in HTW, but concentrating on aliphatic and aromatic amides [8,[12][13][14][15][16][17][18][19][20][21][22][23]. The hydrolysis of heterocyclic amides in HTW is rarely reported.…”
Section: Introductionmentioning
confidence: 97%
“…Hydrolysis of amides in sub- and supercritical water is an important reaction not only as a fundamental acid/base reaction but also as a model reaction for the degradation of proteins and pharmaceuticals. Several studies on this reaction in homogeneous , and heterogeneous catalysis systems have been reported. In general, the hydrolysis of amides at low temperatures proceeds in the presence of homogeneous acid or base catalysts .…”
Section: Introductionmentioning
confidence: 99%
“…In general, the hydrolysis of amides at low temperatures proceeds in the presence of homogeneous acid or base catalysts . Conversely, the hydrolysis of amides has been reported to proceed even in the absence of catalyst in sub- and supercritical water. , Although the reaction mechanism in sub- and supercritical water has not been elucidated sufficiently, some researchers have investigated the reaction mechanism through kinetic experiments. For example, Lee and Gloyna investigated the hydrolysis of acetamide and reported that the reaction was first order with respect to acetamide .…”
Section: Introductionmentioning
confidence: 99%